HAK WARIS ANAK HASIL PERNIKAHAN SIRI DI DESA KALISAT KECAMATAN REMBANG KABUPATEN PASURUAN - Fitrotin Jamilah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2017)
Son is the saving grace of Almighty God, every child has the right in this world began he was born until he died. Kids would say legitimate child of the law if the child was born of a legal marriage under Islamic law and is also listed in the VAT (Nikah Registrars Employees) local district religious affairs office. This will affect the rights of children, ranging from the rights of the state administration, the community and also in terms of inheritance. Marriage according to villagers Kalisat District of Rembang, is a bond between a man and a woman who qualifies and harmonious marriage. Marriage should be done according to Islamic law, according to Islamic law invalid, the wedding was also legitimate in the eyes of the public. Child marriage was also the result of a legitimate child in religion, as a result of child marriage in the register at the local KUA. If the child was born out of the marriage siri is often the case in the village Kalisat District of Rembang, then there will be questions. How does the existence of the child of unregistered marriages in rural districts Kalisat Rembang Pasuruan. How the inheritance rights of children results from a wedding in the village Kalisat series Pasuruan Rembang sub-district. This research uses quantitative research methods.